Can a 'living wage' springboard human capability? An exploratory study from New Zealand. (2nd January 2016) - Carr, Stuart C.; Parker, Jane; Arrowsmith, James; Watters, Paul; Jones, Harvey
ABSTRACT: 'Living' wage campaigns are more than calls for higher basic minima rates of pay. They are predicated on the notion that there is a discrete income below which people risk further deprivation, but above which there should be a qualitative upward shift in human capability. Problematically, however, the theory of diminishing marginal returns predicts that the function linking freedom from deprivation with income will form a smooth curve with no clear pivot (i.e. no discrete 'living' wage at all). Living wages thus remain controversial in that tests of these competing views are rare. A cross-sectional online survey of over 1000 working adults in New Zealand was undertaken to explore these two competing propositions. Household income was compared with measures of life and work capability. It emerged that the function linking life and work capabilities to household income was 'spiked' rather than continuous; the spike traversed scalar midpoints (e.g. from job dissatisfaction to satisfaction), making the shift qualitative (because dissatisfaction is qualitatively different from satisfaction) and the pivot point coincided with more people reporting having enough (versus insufficient) incomes to meet their basic needs. These findings are consistent with the arguments that there is a wage above which workers can begin to develop their capabilities rather than their being no such income point as suggested by the theory of diminishing marginal returns. Its existence has implications for public policy makers, and for wage theory.